2013
DOI: 10.1371/journal.pone.0083273
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Albuminuria in the Korean Adult Population: The 2011 Korea National Health and Nutrition Examination Survey

Abstract: BackgroundMicroalbuminuria is associated with increased risk of renal disease and cardiovascular diseases even in non-diabetic subjects. High incidence rates of microalbuminuria have been found in a number of population-based studies. However, the prevalence and risk factors associated with microalbuminuria in the general population in Korea are unclear.ObjectivesThe present study was performed to estimate the prevalence of microalbuminuria and investigate the associated risk factors in the general adult popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 36 publications
2
35
2
6
Order By: Relevance
“…Since, unlike OAG, diabetic neovascular glaucoma occurs secondary to obstruction of the trabecular meshwork by neovascular membrane that develops in response to retinal ischemia, we confined the study population to nondiabetic subjects. The weighted prevalences of microalbuminuria and macroalbuminuria in this study were found to be lower than those previously reported (5.2% for microalbuminuria and 1.0% for macroalbuminuria), as the previous study did not exclude diabetic patients [21]. The percentages of OAG increased in accordance with increasing UACR tertiles.…”
Section: Discussioncontrasting
confidence: 73%
“…Since, unlike OAG, diabetic neovascular glaucoma occurs secondary to obstruction of the trabecular meshwork by neovascular membrane that develops in response to retinal ischemia, we confined the study population to nondiabetic subjects. The weighted prevalences of microalbuminuria and macroalbuminuria in this study were found to be lower than those previously reported (5.2% for microalbuminuria and 1.0% for macroalbuminuria), as the previous study did not exclude diabetic patients [21]. The percentages of OAG increased in accordance with increasing UACR tertiles.…”
Section: Discussioncontrasting
confidence: 73%
“…Age was also significantly correlated with urinary albumin excretion in the below median endostatin group, but this correlation had only marginal significance in the above median group. In population studies that included diabetic patients, both age and fasting plasma glucose were independently associated with urinary albumin excretion [34,35]. However, in a prospective study of type 2 diabetic patients, not age but fasting plasma glucose was shown to be an independent risk factor for the development of micro-and macroalbuminuria [36].…”
Section: Discussionmentioning
confidence: 99%
“…We found a significant positive association between albuminuria and FRS, even for levels that were below the traditional cutoff value for microalbuminuria, and this association remained after adjusting for conditions potentially affecting the results, including traditional and nontraditional CVD risk factors. Hypertension has a known positive correlation with albuminuria [26]. After adjusting for hypertension history, the association was attenuated, but it remained significant.…”
Section: Discussionmentioning
confidence: 99%